2016
DOI: 10.5493/wjem.v6.i4.72
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of human embryonic stem cells into mature neurons under in vitro culture conditions

Abstract: AIMTo describe the morphogenesis of different neuronal cells from the human embryonic stem cell (hESC) line, SCT-N, under in vitro culture conditions.METHODSThe directed neuronal cell line was produced from a single, spare, pre-implantation stage fertilized ovum that was obtained during a natural in vitro fertilization process. The hESCs were cultured and maintained as per our proprietary in-house technology in a Good Manufacturing Practice, Good Laboratory Practice and Good Tissue Practice compliant laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It was found that these multipotent NPCs differentiated into all three types of cells of the nervous system, i.e., neurons, oligodendrocytes, and astrocytes, as observed under a phase contrast microscope. 88 …”
Section: Introductionmentioning
confidence: 99%
“…It was found that these multipotent NPCs differentiated into all three types of cells of the nervous system, i.e., neurons, oligodendrocytes, and astrocytes, as observed under a phase contrast microscope. 88 …”
Section: Introductionmentioning
confidence: 99%